Kernel weight in maize: genetic control of its physiological and compositional determinants in a dent × flint-caribbean RIL population - Mandolino, Cecilia Ines; D´Andrea, Karina Elizabeth; Piedra, Carlina V.; Alvarez Prado, Santiago; Olmos, Sofía Eugenia; Cirilo, Alfredo Gabriel; Otegui, María Elena (Maydica-ist Sper Cerealicoltur, 2023)
The genetic control of maize kernel weight (KW) determination could be studied through its physiological and/ or compositional determinants. Our objective was to dissect the genetic control of maize KW by analyzing its physiological (KGR: kernel growth rate; KFD: kernel filling duration) and compositional (protein, oil, starch) determinants in a dent×flint Caribbean RIL population, which combines a broad genetic background with grains of high added value for industry. An additional objective was to determine the stability of the genetic control under contrasting growing conditions, for which soil nitrogen offer was modified across experiments. Heritability (H2) values were high for KW (H2 = 0.74) and intermediate for the other traits (from 0.62 to 0.42). Kernel weight had a strong correlation with KFD (r = 0.69), KGR (r = 0.60) and protein concentration (r = 0.56). Ten joint QTL with inconsistent effects across years and seven epistatic interactions were detected. Despite changes in effect size, most QTL were significant under both environments. Nine QTL were associated with variations in potential KW (KWP), mean KW, KGR and oil concentration, eight with variations in protein and starch concentration and seven with KFD. Epistatic interactions were related to regions with significant main effects. The most important finding was the existence of a common QTL for KWP, KGR and KFD on chromosome 5, for which there was no previous report. Results increased our knowledge on the genetic control of KW through its phenotypic and genetic correlation with KFD, confirming the need to explore different physiological strategies in different genetic backgrounds.